KONSEP MODERASI BERAGAMA PERSPEKTIF KI HAJAR DEWANTARA - Arsy, Dzikri Dinikal; Sa’adah, Nihayatus; Al Hakim, Tamara Diina (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
Religious diversity in the archipelago is a gift in itself that should be understood by every citizen so that they can determine how to behave properly according to the situation and condition of the surrounding environment. Taking a stance cannot be done instantly without learning and understanding religious diversity itself. What kind of efforts will be chosen will then become the most important point in reducing and preventing major conflicts and divisions that are contrary to the ideals of this nation. There has been a lot of discussion about religious moderation as one of the keys to peace in the midst of diversity. Like the father of Indonesian education, Ki Hajar Dewantara through his writings and works about the world of education which does not specifically address the issue of religious moderation, but the meaning and implied message in it has an important influence as a supporter of the realization of religious moderation in Indonesia. Through his methods and literature research on his thoughts, we can see that family education, religious teaching in schools, forms of practice of etiquette and manners can open a way out of the impasse that has been faced so far so that what is expected from various moderation can produce maximum results. in the midst of this country's religious diversity. Abstrak Keberagaman beragama di bumi nusantara merupakan sebuah anugerah tersendiri yang seharusnya dipahami oleh setiap warga negara sehingga dapat menentukan cara bersikap yang baik sebagaimana situasi dan kondisi lingkungan sekitarnya. Pengambilan sikap tidak dapat dilakukan secara instan tanpa adanya upaya pembelajaran dan pemahaman akan keberagaman beragama itu sendiri. Upaya seperti apa yang akan dipilih kemudian menjadi poin terpenting dalam meredam dan mencegah konflik besar serta perpecahan yang bertolak belakang dengan cita – cita bangsa ini. Telah banyak perbincangan akan moderasi beragama sebagai salah satu kunci kedamaian di tengah keberagaman. Seperti halnya bapak pendidikan Indonesia, Ki Hajar Dewantara lewat tulisan dan karya – karyanya tentang dunia pendidikan yang memang tidak spesifik menyinggung persoalan moderasi beragama namun makna dan pesan tersirat di dalamnya memiliki pengaruh penting sebagai penunjang terwujudnya moderasi beragama di Indonesia. Lewat metode dan riset pustaka terhadap pemikiran beliau dapat kita ketahui bahwasanya pendidikan keluarga, pengajaran agama dalam sekolah, bentuk praktik ilmu adab dan budi pekerti dapat membuka jalan keluar dari kebuntuan yang selama ini dihadapi, sehingga apa yang diharapkan dari moderasi beragam dapat membuahkan hasil yang maksimal di tengah keberagaman beragama negeri ini.